PEMBATASAN KEPEMIMPINAN PEREMPUAN (Kritik Terhadap Hadist Misoginis) - M. Syaeful Bahar (MUWAZAH : jurnal kajian gender, 2009)
Women's leadership in politics is still a clash of ideas among the scholars’. Some say there are haram (forbidden) and vice versa can say. If this I analyzed further, take note that the main problem actually arises because the interpretation of religious doctrine carried out at shallow So that finally, was born a misoginis interpretation of religious texts, which in this context is the Hadith texts.